From Digital Literacy to Saving Interest: Analysis of the Influence of Brand Image as a Moderating Factor in Account Opening at Bank Sumut Syariah Sibolga: Dari Literasi Digital ke Minat Menabung: Analisis Pengaruh Brand Image sebagai Moderasi dalam Pembukaan Rekening di Bank Sumut Syariah Sibolga - Sarah Febrian; Muhammad Syahbudi; Kusmilawaty (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The development of digital technology has driven significant changes in people's financial behavior, including saving habits and account opening at banking institutions. This study aims to analyze the effect of digital literacy on saving interest and the role of brand image as a moderating variable in account opening. The research employs a quantitative method with a moderation regression approach, based on data collected from 100 respondents who have access to banking services in Indonesia. The results indicate that digital literacy has a positive and significant effect on saving interest. Furthermore, brand image strengthens the relationship between digital literacy and saving interest, suggesting that a positive perception of banking institutions can enhance the trust of potential customers.